The Language of Pandemic and its Significance in Effective Communication - Haji Sismat, Muhamad Alif (Journal of Humanities and Social Sciences Studies, 2021)
Effective communication is vital in delivering information to the public, particularly during the COVID-19 pandemic, to prevent misinformation that would trigger negative emotions. Pandemic-related terms often offer both positive and negative connotations. Therefore, word choice is crucial in ensuring that the information is understandable and relevant. These two significant criteria are two of the six principles for effective communication outlined by the World Health Organisation (WHO). The present study examines the significance of the language used during the pandemic in influencing current communication effectiveness. Therefore, an online questionnaire was designed and then distributed to Malay students at Sultan Sharif Ali Islamic University to know their perceptions of pandemic-related information in Malay and English. The respondents felt that the available information is clearly explained, concise, and relevant to the current situation based on the findings. Regardless of their English language proficiency, most of them are well-aware of the English terms. However, they prefer the information is available in their first language.